Mass Identification in Mammography Images Using K Means Classifier - S. , Kesavan; G. , Charlyn Pushpa Latha (International Journal of Psychosocial Rehabilitation, 2020)
Breast cancer is the most frequently recognized malignancy among ladies and the significant purpose behind the expanded death rate among ladies. As the determination of this infection physically takes extended periods and the lesser accessibility of frameworks, there is a need to build up the programmed determination framework for early recognition of malignant growth. Information mining methods contribute a ton to the improvement of such a framework. For the order of favorable and threatening tumors, we have utilized order strategies of AI in which the machine is found out from past information and can anticipate the classification of new information. This paper is a relative investigation on the usage of models utilizing logistic regression, support vector machines, and K-nearest neighbor, which is done on the dataset taken from the UCI storehouse. As for the aftereffects of exactness, accuracy, affectability, particularity, and false positive rate, the proficiency of every calculation is estimated and looked at. These systems are coded in Python and executed in Spyder, the Scientific Python Advancement Environment. We induce from our examination that SVM is the appropriate calculation for forecasting, and in general KNN is introduced well by SVM.